The influence of green perceived value, green perceived risk, and green trust on green repurchase intention on clodi (clothing diapers) Ningrat - Pertiwi Harly Putri; Rahmiati Rahmiati (Marketing Management Studies, 2022)
The purpose of this study is to analyze: (1) The effect of Green Perceived Value on Green Trust. (2) The Effect of Green Perceived Risk on Green Trust. (3) Effect of Green Trust on Green Repurchase Intention. (4) The Effect of Green Perceived Value on Green Repurchase Intention. (5) Effect of Green Perceived Risk on Green Repurchase Intention. The population in this study was Clodi Ningrat consumers in the city of Padang. The sampling technique in this study is purposive sampling with a total sample of 190 respondents in 2021. The analysis in this study uses SmartPLS 3.0. The results of this study are: (1) Green Perceived Value has a significant and positive effect on Green Trust. (2) Green Perceived Risk has a significant and negative effect on Green Trust. (3) Green Trust has a significant and positive effect on Green Repurchase Intention. (4) Green Perceived Value has a significant and positive effect on Green Repurchase Intention. (5) Green Perceived Risk has a significant and negative effect on Green Repurchase Intention.